Neurobehavioral Abnormalities Associated with Executive Dysfunction after Traumatic Brain Injury - Wood, Rodger Ll.; Worthington, Andrew (Frontiers in Behavioral Neuroscience, 2017)
Objective: This paper will address how anomalies of executive function after TBI can translate into altered social behaviour that has an impact on a person’s capacity to live safely and independently in the community. Method: Review of literature on executive and neurobehavioural function linked to cognitive ageing in neurologically healthy populations and late neurocognitive effects of serious traumatic brain injury (TBI). Information was collated from internet searches involving MEDLINE, PubMed, PyscINFO and Google Scholar as well as the authors’ own catalogues. Conclusions: The conventional distinction between cognitive and emotional-behavioural sequelae of TBI is shown to be superficial in the light of increasing evidence that executive skills are critical for integrating and appraising environmental events in terms of cognitive, emotional and social significance. This is undertaken through multiple fronto-subcortical pathways within which it is possible to identify a predominantly dorsolateral network that subserves executive control of attention and cognition (so-called cold executive processes) and orbito-frontal/ventro-medial pathways that underpin the hot executive skills that drive much of behaviour in daily life. Traumatic brain injury frequently involves disruption to both sets of executive functions but research is increasingly demonstrating the role of hot executive deficits underpinning a wide range of neurobehavioural disorders that compromise relationships, functional independence and mental capacity in daily life.